Governance of the COVID-19 Pandemic in Slovakia - Figulová, Andrea; Dénešová, Michaela (PARTECIPAZIONE E CONFLITTO, 2021)
This paper analyses presence of populistic rhetoric in the behaviour of two Slovak prime ministers who have been responsible for managing the COVID-19 pandemic. It is based on Brubaker's (2017) work on populism and tries to identify his six elements within the area studied. The main argument is that even though these two actors have different political backgrounds and experience, both use a populist repertoire in their communication and actions and having to deal with a crisis such as COVID-19 pandemic is not the reason to not use it. It is important to analyse societal structures as the COVID-19 pandemic not only put lives at risk, but also economic and social rights and the security of the state.